Assessment of the mean dose of the pharyngeal constrictor muscles (as one organ) as a part of DARS and its effect on dysphagia in IMRT treated head and neck cancer patients - May Gamal Ashour; Tarek Hamed Shouman; Ashraf Hamed Hassouna; Maha Hassan Mokhtar; Dalia Abdelfatah (Oral Oncology Reports)
Objective: To assess the mean dose the pharyngeal constrictor muscle (PCM) received and its effect on dysphagia and develop a cut-off value for its occurrence. Methods: 116 patients with head and neck cancer who required bilateral neck irradiation treated using the simultaneous integrated boost IMRT technique were retrospectively evaluated. Pharyngeal constrictor (superior, middle, inferior) and cricopharyngeus and esophageal inlet muscles (cricopharyngeal inlet) were considered dysphagia/aspiration-related structures (DARS) and were summated as one organ at risk structure PCM. PlanPCM consists of the sum of one or multiple pharyngeal constrictor muscles away from high-risk volumes. Results: This study enrolled 116 patients (37 female, 79 male), mean age of 51 years. The mean dose to PCM was 51.37 Gy ± SD (range, 30.08–63.86 Gy). The severity of dysphagia correlated significantly with the dose received by PlanPCM (p < 0.001). The mean dose to PlanPCM in the nasopharyngeal primary was 53.3 Gy (Range 44–63.5 Gy), while it was 45.4 Gy (Range 30.1–56.3 Gy) for laryngeal primaries. Our findings indicated that a dose exceeding 50 Gy to the PlanPCM was more likely associated with high occurrence of dysphagia at one year after the completion of treatment. Conclusion: We reported that PCM delineation as a single structure with sparing the part outside the high risk volumes is more reproducible and leads to the same outcomes if delineated separately.